The information search process of Diliman Preparatory School third year students - Ortega, Angelez P.; Faderon, Rosalie B.; Mallari, Florenda D. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Information seeking is defined by Marchionni (1995) as a process in which humans purposely engage in order to change their state of knowledge. Information seeking is a process of construction that begins with uncertainty and anxiety. The user's experience in the process of information seeking needed to be carefully investigated. This study attempted to replicate Kuhltau's model of the Information Search Process (ISP).
Thirty-eight participants and their teacher for the academic year (2004-2005) participated in the study. Quantitative Process survey and Teacher's Assessment of Focus were utilized in gathering the needed information. To verify the Model of the Information Search Process, quantitative analysis and replication method were used. Likewise, two methods were applied for preparing the data for analysis. One, the nominal data was treated as ordinal, assumed-level data in order to perform statistical measures. The order is that open-ended responses were coded into categorical data for data analysis.
Results of the survey reveal that the responses indicated that thoughts about the topic became clearer and more focused as respondents moved through the search process seeking more pertinent and focused information. It can be surmised that as the information search process moved through, the information became clearer. It can be supported by the data that 13 of the respondents have a "general description of the topic" during the initiation process; it became 19 during the Midpoint process and Closure processes.
Twenty-four of the respondents had "unclear description of the topic" during the Initiation process and eventually narrowed down to 2 during the Closure process. Responses revealed confidence steadily increasing with lowest confidence at Initiation, confidence rising significantly at Midpoint, and with more significant increase at Closure.
In general, the findings indicate that the participants' thoughts about their topics became clearer and more focused as they moved through the search process seeking more relevant and focused information. Feelings accompanying the changes in thoughts matched those predicted in the model, with confidence steadily increasing. Uncertainty, confusion, and frustration decreased during the process as feelings of being satisfied, sure and relieved increased.
Based on the conclusions of the study, the researcher recommended the following measures: a) assessment of perceptions of respondents must be done more often and regular monitoring of a research study to determine success or failure of information search process; b) the model of the information search process needed to be verified in a larger more diverse sample of library users; and c) the researcher strongly recommends that the findings of this study be validated by doing some longitudinal studies in the near future.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Information storage and retrieval systems -- Philippines -- Quezon City; Information services -- Philippines -- Quezon City; High school students -- Philippines -- Quezon City